A new modified extragradient method with Bregman divergence - Semenov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
A new method of the extragradient type for the approximate solution of variational inequalities with pseu-domonotone and Lipschitz-continuous operators acting in a finite-dimensional linear normed space is proposed. This method is a modification of the subgradient extragradient algorithm using the Bregman divergence instead of the Euclidean distance. A theorem on the convergence of the method is proved, and, in the case of a monotone operator, non-asymptotic estimates of the effectiveness of the method are obtained.